A Phenomenological Exploration Of Mindful Consumption Patterns Among Gen Z Consumers In Urban Environments - Nurhadi, Nurhadi (Doctoral Program of Social Science Pasundan University, 2025)
This research investigates the profound shift in purchasing behavior among Generation Z individuals residing in densely populated urban centers, focusing on the emergence of mindful consumption as a core lifestyle choice. While modern marketing literature often portrays this demographic as impulsive and digitally driven, this study employs a transcendental phenomenological approach to uncover the lived experiences and deeper philosophical motivations behind their conscious decision to consume less and more intentionally. Through in-depth, semi-structured interviews with young consumers in major metropolitan areas, the study explores how the pressures of urban consumerism and the constant influx of digital advertisements trigger a reflective transition toward mindfulness. The findings reveal that mindful consumption for Gen Z is not merely an environmental statement but a complex negotiation of identity and a form of resistance against the fast-paced, throwaway culture prevalent in city life. Participants described a journey of